PENGARUH LIQUIDITY, FIRM SIZE, GROWTH OPPORTUNITY, FINANCIAL DISTRESS, LEVERAGE DAN MANAGERIAL OWNERSHIP TERHADAP AKTIVITAS HEDGING DENGAN INSTRUMEN DERIVATIF (Studi Kasus Pada Perusahaan Nonfinansial Yang Terdaftar Di BEI Periode 2010-2014) - Sianturi, Crissy Norris; Demi Pangestuti, Irene Rini (Diponegoro Journal of Management, 2015)
Hedging by using derivative instruments is one of the common risk management used by company to protect their assets from risk of exchange rate and interest rates. This study aimed to determine the effect of liquidity, firm size, theÂ  growth opportunity, financial distress, leverage and managerial ownership on hedging activity using derivative instruments at non-financial companies listed on the Indonesia Stock Exchange in 2010-2014.The population of the study is a data non-financial companies listed on Indonesia Stock Exchange in 2010-2014 The sample in this study amounted to 93 companies by using purposive sampling. This study using logistic regression analysis techniques, to determine the variables that affect of the use of derivative instruments as hedging activity.The results of this study showed that there are three variables that affect significantly hedging activity using derivative instruments. Variable firm size and leverage have positive affect on hedging activity using derivative instruments, and variable financial distress have negative affect on hedging activity using derivative instruments. Whereas for the other variables did not influence the hedging activity using derivative instruments.